2015
DOI: 10.1016/j.physd.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Transitions between streamline topologies of structurally stable Hamiltonian flows in multiply connected domains

Abstract: h i g h l i g h t s• A combinatorial procedure providing a list of possible transitions between streamline topologies. • It is applicable to any physical phenomena described by 2D Hamiltonian vector fields.• It provides many global and generic transitions between streamline topologies. • It is applicable to snapshots of streamline patterns observed experimentally. • A new data compression algorithm for a large amount of long-time flow evolution data. a b s t r a c tWe consider Hamiltonian vector fields with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The theory has been extended to the structurally stable Hamiltonian flows in the presence of a uniform flow and solid boundaries [22], in which it is additionally shown that every streamline topology of structurally stable Hamiltonian vector fields is represented by a sequence of letters, called a maximal word. Furthermore, it is found that streamline topology of orbit structures are in one-to-one correspondence with labeled directed rooted trees [20].…”
Section: Introductionmentioning
confidence: 99%
“…The theory has been extended to the structurally stable Hamiltonian flows in the presence of a uniform flow and solid boundaries [22], in which it is additionally shown that every streamline topology of structurally stable Hamiltonian vector fields is represented by a sequence of letters, called a maximal word. Furthermore, it is found that streamline topology of orbit structures are in one-to-one correspondence with labeled directed rooted trees [20].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the topologies of such fluids also can be changed by switching combinatorial structures of separatrices. In the codimension zero and one cases, such graph structures are characterized [5,6,7,9,10]. In particular, vertices correspond to structurally stable Hamiltonian vector fields and edges correspond to "generic" intermediate vector fields.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between Hamiltonian and area-preserving flows on closed surfaces can be represented by harmonic flows, which are generated by the dual vector fields of harmonic one-forms. The topological invariants of Hamiltonian flows with finitely many singular points on compact surfaces are constructed from integrable systems points and dynamical systems points of views, and the structural stability are characterized [5,20,25,27,28,34]. On the other hand, any area-preserving flows are non-wandering flows.…”
Section: Introductionmentioning
confidence: 99%